Effectiveness of the anti-malaria campaign in Sri lanka - Wickramasinghe, W.K (My University, 2008)
A descriptive cross sectional study covering 18 "malaria districts' of the country was carried out in order to ascertain effectiveness of the malaria control program in Sri Lanka. The districts with malaria risk were divided into two groups, as high risk and low risk districts. The study had three components, the facility assessment included resources, control prevention, case detection treatment and management, the outcome assessment included outcome of control prevention activities and morbidity mortality, the assessment of public awareness and satisfaction included knowledge attitudes and practices and satisfaction over malaria control activities. Many districts had not carried out entomological visits in adequate numbers, and standard activities for vector control activities there were large differences among districts. Batticaloa district is largely depended on Indoor Residual Spraying and neglected larval control activities, insecticidal treatment of bed-nets etc. Distribution of Long Lasting Insecticidal Nets was limited to districts of Northern, North central, North Western and Eastern provinces. Majority of patients interviewed were having good level of Knowledge, attitudes and practices. though majority 0 patients trusted health services the study showed that such important areas of satisfaction as communication and autonomy have to be improved. Satisfaction of patients from different hospitals differed in areas such as dignity, autonomy, comfort, confidentiality. This showed that services rendered in different hospitals studied are varying and interventions needed. The study highlighted certain other deficiencies that have to be corrected and necessary recommendations were done. The malaria situation in Northern Province except in one district was not assessed by the study and it is recommended to study those districts also to reveal real situation prevailing there.